Innovative Leadership Model for Healthcare Teams - Hoffman-Simen, Janice (Medical Research Archives, 2023)
Background: Healthcare teams possess multiple clinical capabilities to meet the demands and challenges of individual patient-centered care. Teams in healthcare have been used for centuries, but the functionality of a team largely depends on the leader facilitating. With the complexities of healthcare, single leadership models often do not apply. This study aimed to complete a multi-method qualitative study looking at four healthcare settings to explore the applicable use of the Simen-Schreiber leadership model to best describe the needs of healthcare teams (ambulatory diabetes clinic; skilled nursing facility [SNF], acute inpatient geriatric-psychiatric unit, and outpatient high-risk geriatric clinic). Methods: The key constructs researched in this mixed-method qualitative study were: 1) skills needed for good healthcare team participation and 2) essential outcomes needed for successful patient-centered care (e.g. communication, interpersonal engagement, and shared decision-making).  The qualitative portion of this study included three distinctive methods: 1) observation of each team functionality; 1,2 2) interview to obtain background information about each facility; and 3) Focus Group session composed of 10 questions and a duration of approximately 75 to 90 minutes. Additional methodology utilized for this study included two validated and reliable quantitative assessments: 1) a healthcare team observation tool 1,2 and 2) emotional intelligence questionnaire. 3 This multi-method, multi-case study design was selected to allow for triangulation of the data to support the seven constructs of the leadership model. The constructs include rotation of the leader; clinical expertise; emotional intelligence; and managerial skills, with the outcomes of communication; interpersonal engagement and share decision-making. Results: There appears to be a slight trend of higher-functioning teams demonstrated higher emotional intelligence scores, according to the TEI-Que questionnaire and the Team Observation Tool results. From the managerial skills perspective, the Focus Groups results suggests that these skills, particularly in time management, are a target area for improvement among all four teams.  Furthermore, these findings support the need to improve training in managerial skills to prepare professionals adequately for healthcare teamwork.  it is widely accepted that, good communication is vital within a healthcare team and is related to positive patient outcomes. Unfortunately, poor communication is seen daily in healthcare and can lead to serious health consequences for the patient and dissatisfaction with care by patients, family members, other caregivers, along with clinicians and other healthcare team members.  Lastly, there appeared to be support from this study that involvement of the patient, family and interprofessional team in the shared decision-making process is helpful for successful patient outcomes. Conclusions: The findings of this study support the Simen-Schreiber leadership model as applicable to healthcare teams. Each healthcare professional should possess clinical expertise, high emotional intelligence and good managerial skills, to be able to best function on a healthcare team.  The Simen-Schreiber leadership model may be useful in preparing healthcare professionals for participation in teamwork, leading to more efficient and effective patient-centered care.